Technology and innovation in healthcare - Sinha, N., Agrawal, N. and Suroor, N. (Kurukshetra)
An effective healthcare system of a nation is determined by its ability to deliver high quality and efficient care that is affordable and accessible for all. Access to quality healthcare is a problem in the country, especially in the hinterland.- Reproduced
Keywords: Technology, Innovation, Healthcare